Tacit knowledge sharing in a Lebanese family business: the influence of organizational structure and tie strength - Awada, Hoda (2025)
Purpose This study explores the influence of organizational structure on relationship formation and tacit knowledge sharing within a family business context. Design/methodology/approach Utilizing a single case study approach, data were collected through interviews and questionnaires from 12 participants at a family-owned advertising and communication firm in Beirut, Lebanon. Findings The research highlights the critical role of organizational structure in enhancing organizational effectiveness through knowledge transfer. It underscores how both intraorganizational and interorganizational ties influence knowledge sharing processes and demonstrates the varying impacts of tie strength on tacit knowledge distribution. Originality/value This paper contributes to the literature by examining the interdependence between organizational structure, tacit knowledge transfer and tie strength in family businesses. By analyzing these elements across internal and external boundaries, the study offers a fresh perspective on network dynamics. The research highlights that traditional definitions of network ties may not fully capture the unique environment of family firms, where structural nuances impact knowledge sharing and performance. Practically, the findings provide actionable insights for managers to design organizational structures that optimize tacit knowledge flow, fostering innovation and competitiveness. This work challenges existing frameworks and offers guidance for improving knowledge management in family businesses, supporting sustainable growth and success.